Search for randall-sundrum gravitons in dilepton and diphoton final states - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Amer Physical Soc, 2005)
We report the first direct search for the Kaluza-Klein (KK) modes of Randall-Sundrum gravitons using dielectron, dimuon, and diphoton events observed with the D0 detector operating at the Fermilab Tevatron p (p) over bar Collider at root s = 1: 96 TeV. No evidence for resonant production of gravitons has been found in the data corresponding to an integrated luminosity of approximate to 260 pb(-1). Lower limits on the mass of the first KK mode at the 95% C. L. have been set between 250 and 785 GeV, depending on its coupling to standard model particles.